2022
DOI: 10.1155/2022/2698845
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of FDM Printing Process Parameters on Surface Finish, Thickness, and Outer Dimension with ABS Polymer Specimens Using Taguchi Orthogonal Array and Genetic Algorithms

Abstract: Fused deposition modelling (FDM) is a technique of additive manufacturing used to fabricate a 3D (three-dimensional) model with layer-by-layer deposition of required materials with less material wastage. FDM is used to make any objects with a meager cost, but also there are some negative points related to less strength, less accuracy, and less surface finish. In this study, acrylonitrile butadiene styrene (ABS) is printed using an FDM printer to investigate the effects of various changing parameters like nozzl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…The studied parameters by the proposed computational model provide insight and understanding of how these process parameters tune the properties such as voids and mechanical properties. To optimize the entire FDM method, the proposed model could be combined with the optimization algorithm enhancing the effectiveness of the model (Chohan et al , 2022; Fountas and Vaxevanidis, 2021; Yodo and Dey, 2021). Future research is directed toward developing the optimized model by using algorithms in conjunction with the developed computational model.…”
Section: Resultsmentioning
confidence: 99%
“…The studied parameters by the proposed computational model provide insight and understanding of how these process parameters tune the properties such as voids and mechanical properties. To optimize the entire FDM method, the proposed model could be combined with the optimization algorithm enhancing the effectiveness of the model (Chohan et al , 2022; Fountas and Vaxevanidis, 2021; Yodo and Dey, 2021). Future research is directed toward developing the optimized model by using algorithms in conjunction with the developed computational model.…”
Section: Resultsmentioning
confidence: 99%
“…A broad range of patterns such as grid, triangle, zigzag (3), and concentric (2) were generated and produced by FDM printers [ 54 ], where pattern 2 showed improved results. Another study [ 62 ] reported that a linear pattern (1) is better than a triangle and tetrahedral pattern. Thus, there was a need to evaluate between pattern “1” and pattern “2”.…”
Section: Resultsmentioning
confidence: 99%
“…The Taguchi method helped determine that the print speed is the most influential printing parameter considering the surface roughness. [ 67 ] Other researchers evaluated 3D-printed parts using coordinate metrology. Yankov et al used an SLA 3D printer to create micro-squares.…”
Section: Methods Of Metrologymentioning
confidence: 99%